Polish political browser games as generative metaphors: analysis of structures and functions - Babecki , Miłosz (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
This article describes a study of 33 Polish political browser games, which are left of the set of 51 applications developed by Polish Internet users from 2005 to 2020. These considerations concern mainly the metaphorical messages conveyed in these games, in particular which features make browser games metaphorical messages, and what game structure is necessary to convey such messages. Differentiation of these game types is equally important. Owing to it, they can participate in expressive and explanatory communication.